2017
DOI: 10.47197/retos.v0i32.52871
|View full text |Cite
|
Sign up to set email alerts
|

Individualized speed threshold to analyze the game running demands in soccer players using GPS technology (Umbral de velocidad individualizado para analizar en jugadores de fútbol mediante tecnología GPS las exigencias de sus desplazamientos en competici

Abstract: The aim of the study was to compare the relative running demands (m·min-1), among different soccer players positions, coded by an absolute threshold vs. an individualized threshold based on splits of 10% of peak velocity, during friendly games, with the same tactical system and monitoring with a GPS. To this end he had 20 players on a semiprofessional soccer team. All players were monitored with a unit GPS (15 hz SPI-pro W2b, GPSport, Canberra, Australia).  They are measured peak velocity with a sprint of 40 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Future studies that individualize speed thresholds using peak velocity of these athletes need to be applied. 28,29 These results are of great practical interest for modern -hockey specific training. However with this study research was not possible to understand whether differences in match high-intensity performance were due to difference in fitness level or due to technical-tactical constraints.…”
Section: Discussionmentioning
confidence: 78%
“…Future studies that individualize speed thresholds using peak velocity of these athletes need to be applied. 28,29 These results are of great practical interest for modern -hockey specific training. However with this study research was not possible to understand whether differences in match high-intensity performance were due to difference in fitness level or due to technical-tactical constraints.…”
Section: Discussionmentioning
confidence: 78%
“…Their results are similar to ours, where the external midfielders present the greatest distances covered, recording 224.4 ± 82.4 m, and the players with the least distance covered were the central defenders (85.1 ± 61.4 m). In the study by Núñez-Sánchez et al (2017) who presents different ranges in this area (> 21 km•h−1), concludes that forwards are the players with the longest travel. Finally, Miñano-Espin et al (2017), in their study with Real Madrid (seasons 2001 to 2007), concluded that at speeds > 24 km•h, the players with the greatest distance covered were the wide defenders (374 ± 144 m), and those with the least distance covered were the central defenders (161 ± 91 m).…”
Section: Discussionmentioning
confidence: 93%
“…Presently, differences in field position and speed characteristics prevent the development of arbitrary sprint zone classifications, 29 and this disparity may be more pronounced in players of CP football due to varying levels of ability, as represented by the classification system that governs the sport 2 . More recently, the use of individualized speed thresholds has been applied to research in various team sports, including rugby and football 20,30 . Similarly, individualized thresholds were applied when exploring time-motion characteristics in the CP football athletes to better understand their relative speeds attained by accounting for varying levels of impairment.…”
Section: Discussionmentioning
confidence: 99%